The Role of Indonesian Students as Agents of Community Change in Learning Activities during the COVID-19 Pandemic - Surya Aymanda Nababan; Pulung Sumantri; Anju Nofarof Hasudungan (East Asian Journal of Multidisciplinary Research, 2023)
The COVID-19 pandemic has made big changes to the human life sector. In order to break the chain of this virus, the government has issued a policy to maintain social distance and all activities must be carried out at home. The purpose of this research is to find out what roles students can play in society as agents of change during the COVID-19 pandemic. In particular, the issues raised in this research are; what is the role of students as agents of change in supporting learning activities during the COVID-19 pandemic. This research resulted in a conclusion that the role of Indonesian students as Agents of Change in the field of education during the COVID-19 pandemic includes; become a facilitator in learning activities, create fun learning, provide education about healthy lifestyles, and impart skills to children.